2021
DOI: 10.1111/cup.14145
|View full text |Cite|
|
Sign up to set email alerts
|

Diverse landscape of dermatologic toxicities from small‐molecule inhibitor cancer therapy

Abstract: Background: Advances in molecular biology and genetics have contributed to breakthrough treatments directed at specific pathways associated with the development of cancer. Small-molecule inhibitors (Nibs) aimed at a variety of cellular pathways have been efficacious; however, they are associated with significant dermatologic toxicities. Methods: We conducted a comprehensive review of dermatologic toxicities associated with Nibs categorized into the following five groups: (a) mitogen-activated protein kinase; (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 7 publications
(12 citation statements)
references
References 338 publications
0
9
0
Order By: Relevance
“…This review aims to be the most comprehensive catalog of the dermatologic toxicity profile of non‐ICI mAb‐based cancer therapies. Compared with those associated with ICIs and Nibs, 12,13,45 we found that the dermatologic toxicities with these non‐ICI mAbs are mostly inflammatory and not typically characterized by histopathologic evaluation (Tables 2 and 3). Inflammatory reactions to mogamulizumab have the most comprehensive histopathologic description among the non‐ICI mAbs and include lichenoid/interface, psoriasiform, spongiotic, and granulomatous morphology and may rarely exhibit vitiligo‐like reactions 125,128–131,188,290 .…”
Section: Discussionmentioning
confidence: 94%
See 2 more Smart Citations
“…This review aims to be the most comprehensive catalog of the dermatologic toxicity profile of non‐ICI mAb‐based cancer therapies. Compared with those associated with ICIs and Nibs, 12,13,45 we found that the dermatologic toxicities with these non‐ICI mAbs are mostly inflammatory and not typically characterized by histopathologic evaluation (Tables 2 and 3). Inflammatory reactions to mogamulizumab have the most comprehensive histopathologic description among the non‐ICI mAbs and include lichenoid/interface, psoriasiform, spongiotic, and granulomatous morphology and may rarely exhibit vitiligo‐like reactions 125,128–131,188,290 .…”
Section: Discussionmentioning
confidence: 94%
“…The emergence of the fields of oncodermatology and oncodermatopathology have led to enhanced awareness of the mucocutaneous reactions associated with cancer therapy and their impact on patients' quality of life 11 . We previously reviewed the dermatologic toxicities associated with cancer therapy using small‐molecule inhibitors (Nibs) or immune checkpoint inhibitors (ICIs), categorizing these toxicities as inflammatory, immunobullous, alterations of epidermal keratinocytes, alterations of epidermal melanocytes, or cutaneous deposits 12,13 . In this review, we provide a comprehensive catalog of dermatologic toxicities associated with non‐ICI mAbs, with particular attention to their histopathologic features.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In patients with delayed cutaneous hypersensitivity drug reactions to imatinib and dasatinib, patch tests at 1%, 5%, and 10% have been used in previous studies [ 9 ]. Small inhibitor molecule therapy with agents similar to TKIs can cause a vast array of dermatologic toxicities, ranging from simple maculopapular rashes to severe reactions such as SCARs [ 10 ].…”
Section: Discussionmentioning
confidence: 99%
“…1 They occur in fewer than 1% of patients treated with targeted inhibitors of BRAF and other small-molecular inhibitors. 1,2 Bullous pemphigoid (BP)-irAE is the most commonly reported autoimmune blistering process among cancer patients treated with anti-programmed cell death protein 1 (PD-1)/programmed death-ligand 1 (PD-L1) and anti-cytotoxic T-lymphocyte-associated protein 4 (CTLA-4) therapies. 3,4 A review of 58 cases of BP-irAE associated with anti-PD-1/PD-L1 immunotherapy demonstrated a median latency of $28 weeks and most often clinical presentation as an eczematous or urticarial lesion or blisters (80%) with a histopathologic pattern of subepidermal bullae (71%) and eosinophils (81%).…”
Section: Introductionmentioning
confidence: 99%